"I definitely felt like I was there": enacting empathy and negotiating a virtual reality Indian Residential School. (September 2022) - Woolford, Andrew; Starzyk, Katherine B; Sinclair, Struan; Muller, Adam; MacDonald, David B
We examine how 20 university students interacted with a virtual Residential School that was designed in partnership with a group of Indigenous Survivors of Canada's Residential Schools system. We begin by offering a brief history of Canada's Residential Schools system as well as the origins and ambitions of the Embodying Empathy project. We also reflect on the idea of empathy as it has been taken up both in the design and testing phases of the project and on how student participants enacted their empathy. We demonstrate how participants worked through their immersion in the virtual Residential School, selecting empathy frames that allowed them to grapple with its content and connect with the Survivor narratives presented therein.